Numerical study of water content distribution and controlling factors in and beneath a railway embankment - Lúcia Pedrosa; Christian Engelmann; Martin Binder; Sabrina Michael; Markus Zingelmann; Traugott Scheytt (Grundwasser, 2026)
As urbanization and transport demands rise, railway systems face higher risks from operational disruptions due to system failures and climate-related impacts, especially in urban areas. Understanding water flow and distribution beneath railway embankments is crucial not only for assessing potential contaminant transport in soil and groundwater but also for identifying possible structural weaknesses. This study implements numerical simulations to investigate these dynamics, focusing on a standard railway embankment designed according to German norms. The model setup includes ballast, a low-permeability protection subgrade surface layer (PSS), a subgrade (embankment base), and a subsurface to a depth of 10 m. Numerical simulations were conducted following a univariate approach. Variation parameters included key hydraulic characteristics of the embankment and subsurface. Further parameters were groundwater recharge rate, groundwater level, existence of a less permeable horizontal layer at multiple depths, and thickness of the embankment. The most sensitive parameters shaping water percolation fronts are identified as empirical coefficients (especially the Van Genuchten shape variable α), groundwater levels and hydraulic conductivity. The results indicate that the PSS layer retains the greatest amount of water from the rail system, particularly beneath the ballast. Low α values (0.8 m –1 to 7.7 m –1 ) led to total retention of water within the embankment, with no visible percolation fronts and the lowest values observed at the PSS layer. Shallow groundwater increased initial water content up to 0.30 at the PSS layer, rapidly approaching near fully water-saturated conditions. Embankments with low hydraulic conductivities (0.048 m d −1 to 1.207 m d −1 ) show the highest water contents, reaching up to 0.46, forming a clogging area prone to retain contaminants.

Optimization of nonviral transfection: variables influencing liposome-mediated gene transfer in proliferating vs. quiescent cells in culture and in vivo using a porcine restenosis model - Jaroslav Pelisek; Markus Engelmann; Adam Golda; Alexandra Fuchs; Sorin Armeanu; Masumi Shimizu; Choukri Mekkaoui; Pierre Rolland; Sigrid Nikol (Journal of Molecular Medicine, 2002)